Assessing thermal comfort and energy efficiency in tropical African offices using the adaptive approach. Issue 5 (4th November 2014) - K. Ahadzie, Divine; A. Ankrah, Nii; O. Efeoma, Meshack; Uduku, Ola
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to adduce the most appropriate thermal comfort assessment method for determining human thermal comfort and energy efficient temperature control in office buildings in tropical West Africa. Design/methodology/approach – This paper examines the Adaptive Thermal Comfort Standard, from its research evolution to its contemporary use as an environmental design assessment Standard. It compares the adaptive component of ASHRAE Standard 55 and the European CEN/EN 15251. It begins by reviewing relevant literature and then produces a comparative analysis of the two standards, before suggesting the most appropriate Adaptive Thermal Comfort Standard for use in assessing conditions in tropical climate conditions. The suggested Standard was then used to analyse data collected from the author's pilot research into thermal conditions, in five office buildings situated in the city of Enugu, South Eastern Nigeria. Findings – The paper provides insight as to why the ASHRAE adaptive model is more suitable for thermal comfort assessment of office buildings in the tropical West African climate. This was demonstrated by using the ASHRAE Thermal Comfort Standard to assess comfort conditions from pilot research study data collected on Nigerian office buildings by the author. Originality/value – The paper compares the adaptive component of ASHRAE Standard 55 with CEN/EN 15251, and their different benefits for use in tropical climates. It suggested the need for further research studies and application of the ASHRAE Adaptive Thermal Comfort Standard in the tropical West African climate.